Contenido nutricional del compost elaborado a partir de residuos de soca de maíz (Zea mays L.) - Hidalgo Zambrano, Kayna Marilyn (2019)
This research evaluated the different composting formulations from corn crop residues, using a completely randomized design with five treatments. The control variables (temperature, pH, CE and NPK) were taken for twelve weeks and subjected to ANOVA statistical analysis and the Duncan test; the results found in the different treatments reflected that the temperature at the beginning of the process ranged between 43,2 to 45,53°C, because the microorganisms began to increase and at the end of the process remained between 26 and 28°C, this variable has a significant effect among treatments (P = 0,015). On the other hand, the pH increased reaching a final value of 8,20 to 8,80 (P = 0,851); the behavior of the electrical conductivity in each of the treatments varied between T1 (1,5 dSm-1), T2 (1,05 dSm-1), T3 (1,2 dSm-1), T4 (0,8 dSm-1) and T5 (1 dSm-1). NPK values showed significant differences (p <0,05) in treatments T2 (46,6%), T3 (33,1%) and T4 (29,5%). The results found in the different treatments and the requirements required by the regulations (Nch2880) are typified in class B with a germination rate of T1 = 60%, T2 =76%, T3= 88% and T4 = 94%, without however, T2 treatment meets all expectations of the maximum permissible limits for macro and micronutrients, being a sustainable alternative that can improve the final disposal of corn crop residues. This was socialized in the Balsa community in the Middle of Bolivar Canton, generating a manual of good environmental practices.